Development Of An Integrated Modal Analysis Application Methodology For Base Pan Finite Element Model Validation - Tan, Thomas Siang Yaw (2017)
Modal analysis is used to helps mechanical engineer to analysis the dynamic properties and behaviour of a structure in term of vibrational excitation with the purpose of finding out roots of vibration failure. Vibration failure is normally caused by the natural frequency and mode shape. When resonance occurs, in serious case, it will lead the structure to crack, and therefore, this research is to develop a modal analysis for a cabinet RHS which is a part for air-conditioner under the free-free vibration. Theoretical results and the experimental result of the mode shape for the cabinet RHS was found in this project and the correlation was done in order to compare between the theoretical result and experimental result. NX software was used to do the geometry clean up and finite element analysis (FEA) on the cabinet RHS in order to find out the mode shape theoretically, moreover, pre-test was also done by using NX software to choose the sensor point in order to proceed to conduct Experimental Modal Analysis (EMA). The experimental result of mode shape of cabinet RHS was obtained by using Impact Hammer Experiment Modal Analysis (EMA) and Shaker Experimenatl Modal Analysis (EMA) in Bruel & Kjaer software and equipment. MAC correlation was done in NX software in order to compare the natural frequency between the FEA result and the EMA result. The result for this project can take as a reference for the air conditioning industry to modify and validate teh cabinet RHS in order to enhance the quality of the product as well as to reduce the cost and time consumption by not doing any further investigation for a physical prototypes.